2007
DOI: 10.1002/mc.20384
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of XRCC1 and the frequency of mutation in codon 249 of the p53 gene in hepatocellular carcinoma among guangxi population, China

Abstract: In hepatocellular carcinoma (HCC), hotspot mutation in codon 249 of the p53 gene has been associated with exposure to aflatoxin B1 (AFB1). While the polymorphism of DNA repair gene X-ray repair cross-complementary group 1 (XRCC1) Arg399Gln may be related with AFB1-DNA adducts and gene mutations. Five hundred one HCCs were included in this study to investigate the role of the XRCC1 codon 399 polymorphism on hotspot mutation in codon 249 of the p53 gene. The genotypes of XRCC1 codon 399 and p53 codon 249 were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
5
32
0
Order By: Relevance
“…Following the literature review, we identified 17 studies for potential inclusion in the meta-analysis; 9 were excluded, comprising 2 review articles (Ye et al, 2006;Huang and Zeng, 2010), 4 repeated reports Long et al, 2005;Wang, 2006;Kiran et al, 2009b), 1 study that examined the association between HCC and SNPs of XRCC1 and p53-249 (Long et al, 2008), 1 study without Hardy-Weinberg equilibrium test (Long et al, 2006), and 1 study that demonstrated an association between HCC related to HBV and an SNP of XRCC1 and glutathione S-transferase (Yu et al, 2003). The remaining 8 studies met our selection criteria and were used for the meta-analysis; 4 were written in Chinese, and 4, in English.…”
Section: Characteristics Of Literaturementioning
confidence: 99%
“…Following the literature review, we identified 17 studies for potential inclusion in the meta-analysis; 9 were excluded, comprising 2 review articles (Ye et al, 2006;Huang and Zeng, 2010), 4 repeated reports Long et al, 2005;Wang, 2006;Kiran et al, 2009b), 1 study that examined the association between HCC and SNPs of XRCC1 and p53-249 (Long et al, 2008), 1 study without Hardy-Weinberg equilibrium test (Long et al, 2006), and 1 study that demonstrated an association between HCC related to HBV and an SNP of XRCC1 and glutathione S-transferase (Yu et al, 2003). The remaining 8 studies met our selection criteria and were used for the meta-analysis; 4 were written in Chinese, and 4, in English.…”
Section: Characteristics Of Literaturementioning
confidence: 99%
“…Among these, five papers (Zhang et al, 2010;Liu et al, 2011;Xie et al, 2012;Li et al, 2013;Zeng et al, 2013) which were meta-analysis papers, four studies which were conducted (Yu et al, 2003;Han et al, 2004;Long , 2004;Han et al, 2012) on the same population, four (Long et al, 2008;Ding et al, 2012;Jung et al, 2012) papers not providing adequate data for calculation of OR and 95% CI, and four Su et al, 2008;Guo et al, 2012;Bose et al, 2013) studies not in accordance with HWE were excluded. A flow diagram summarizing the process of study selection was illustrated in Figure 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…It is generally accepted that genetic factors play a key role in the pathogenesis of HCC (Thorgeirsson and Grisham, 2002;Nault and Zucman-Rossi, 2011). Because XRCC1 is potentially one of the most important genes implicated in HCC, a large number of association studies have been conducted in recent years to evaluate the role of Arg194Trp, Arg280His and Arg399Gln polymorphisms in XRCC1 on the risk of HCC (Rossit et al, 2002;Yu et al, 2003;Long et al, 2008;Kiran et al, 2009a,b;Pan et al, 2011;Han et al, 2012;Li et al, 2012). The results of these association studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the human X-ray repair complementing defective repair in Chinese hamster cells 1 gene (XRCC1) was potentially an important gene influencing the risk of HCC (Rossit et al, 2002;Yu et al, 2003;Chen et al, 2005;Kirk et al, 2005;Borentain et al, 2007;Long et al, 2006Long et al, , 2008Kiran et al, 2009a,b;Liu et al, 2011;Pan et al, 2011;Han et al, 2012;Li et al, 2012). A number of single nucleotide polymorphisms (SNPs) have been identified in XRCC1, such as arg inine(Arg)194tryptophan(Trp), Arg280histidine(His), and Arg399glutamine(Gln) (Rossit et al, 2002;Yu et al, 2003;Long et al, 2008;Kiran et al, 2009a,b;Pan et al, 2011;Han et al, 2012;Li et al, 2012). Furthermore, several studies proved that XRCC1 polymorphisms were associated with HCC (Rossit et al, 2002;Yu et al, 2003;Long et al, 2008;Kiran et al, 2009a,b;Pan et al, 2011;Han et al, 2012;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation